Altered Tim-1 and IL-10 Expression in Regulatory B Cell Subsets in Type 1 Diabetes - Liu, Yikai; Chen, Zhiying; Qiu, Junlin; Chen, Hongzhi; Zhou, Zhiguang (Frontiers in Immunology, 2021)
Abstract Background Type 1 diabetes (T1D) is an autoimmune disease with a complex aetiology. B cells play an important role in the pathogenesis of T1D. Regulatory B cells (Bregs) are a subset of B cells that produce and secrete the inhibitory factor interleukin-10 (IL-10), thereby exerting an anti-inflammatory effect. It was recently discovered that T-cell immunoglobulin mucin domain 1 (Tim-1) is essential for maintaining Breg function related to immune tolerance. However, the detailed understanding of Tim-1+ Bregs and IL-10+ Bregs in T1D patients remains incomplete. This study aimed to characterize the profile of B cell subsets in T1D patients compared with that in controls and determine whether Tim-1+ Bregs and IL-10+ Bregs play roles in T1D. Materials and Methods A total of 24 patients with T1D and 24 healthy controls were recruited for this study. Flow cytometry was used to measure the levels of different B cell subsets (including B cells, plasmablasts, and Bregs) in the peripheral blood. Radiobinding assays were performed to detect the antibody titres of T1D patients. In addition, the correlations between different B cell subsets and patient parameters were investigated. Results Compared with healthy controls, there is no difference in the expression level of B cells in peripheral blood mononuclear cell (PBMC) from patients with T1D, expression levels of Tim-1+ Bregs were significantly decreased in patients with T1D (37.76±7.2 vs. 42.25±6.834, P=0.03*), while expression levels of IL-10+ Bregs were lower than healthy controls (17.36±6.345 vs. 24.52±11.69, P=0.01*), the frequencis of total Bregs in PBMC also decreased in patients with T1D (1.42±0.42 vs. 1.99±0.93, P=0.01*). We analyses whether these alterations in B cells subset were associated with clinical features. The frequency of Bregs was negatively related to fasting blood glucose (FBG) (r=-0.30, P=0.04*). The frequency of IL-10+ Bregs was negatively correlating with FBG and HbA1c (r=-0.35 and -0.30; P=0.02* and 0.04*, respectively)and positively correlated with first C-peptide (FCP) (r=0.37, P=0.01*), There was negative correlation between the frequency of B cells and FCP (r=-0.34, P=0.02*). Moverover, it is worth noting that our study did not observe any correlations between B cell subsets and autoantibody titres.